PENGARUH PEMAHAMAN RED FLAG TERHADAP DETEKSI KECURANGAN DENGAN PENGALAMAN AUDITOR SEBAGAI VARIABEL MODERASI - Fakhmi Zakaria; Linda Ayu Oktoriza; Suhita Whini Setyahuni; Rissa Anandita (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
The purpose of this research is to investigate the impact of red flags on fraud detection, the impact of auditor experience on fraud detection, and the capacity of auditor experience to mitigate the impact of red flags on fraud detection. This study's sample included 57 auditors from the Central Java Provincial Regional Inspectorate. This is quantitative research. Partial Least Squares (PLS) analysis is utilized for data analysis, and SmartPLS software is employed. According to the study's findings, red flags have a strong positive influence on fraud detection, auditor experience has a significant effect on fraud detection, and auditor experience cannot attenuate the effect of comprehending red flags on fraud detection.